Peran Gugus Tugas Reforma Agraria Terhadap Konflik Tanah Bekas Lapangan Terbang di Nagari Gadut Kabupaten Agam - Ridho Darman (Diploma IV Pertanahan Sekolah Tinggi Pertanahan Nasional, 2026)
This study aims to analyze the role of the Agrarian Reform Task Force (GTRA) in resolving land conflicts over the former airfield area in Nagari Gadut, Tilatang Kamang Subdistrict. The conflict stems from overlapping claims of control between the government and local communities over military land that has long been utilized by residents for agricultural, residential, and social purposes. This research employs a descriptive qualitative method with a case study approach. Data were collected through document analysis of the 2022 official report of the GTRA of Agam Regency, mapping results of Agrarian Reform Object Land (TORA), and various policy documents related to agrarian reform. The findings reveal that the GTRA of Agam Regency plays a crucial role as a cross-sectoral coordination facilitator, a mediator in non-litigation conflict resolution, and a formulator of land redistribution policy recommendations. The mapping results indicate that most of the land has been productively used by the community. However, the implementation of agrarian reform still faces several obstacles, including overlapping state asset data and limited authority of local GTRA institutions, as well as insufficient support in terms of resources and information systems. Conceptually, resolving the conflict in Nagari Gadut requires synergy between asset and access restructuring involving the central GTRA, local government, and community stakeholders. Penelitian ini bertujuan untuk menganalisis peran Gugus Tugas Reforma Agraria (GTRA) dalam penyelesaian konflik pertanahan area bekas lapangan terbang di Nagari Gadut, Kecamatan Tilatang Kamang. Konflik tersebut berasal dari tumpang tindih klaim penguasaan antara pemerintah dan masyarakat atas tanah aset militer yang telah lama dimanfaatkan warga untuk kepentingan pertanian, permukiman, dan fasilitas sosial. Penelitian ini menggunakan metode kualitatif deskriptif dengan pendekatan studi kasus. Data diperoleh melalui studi dokumentasi terhadap laporan resmi GTRA Kabupaten Agam Tahun 2022, peta hasil pendataan Tanah Objek Reforma Agraria (TORA), serta berbagai dokumen kebijakan reforma agraria. Hasil penelitian menunjukkan bahwa GTRA Kabupaten Agam berperan penting sebagai fasilitator koordinasi lintas sektor, mediator penyelesaian konflik non-litigasi, dan penyusun rekomendasi kebijakan redistribusi tanah. Pendataan menunjukkan sebagian besar lahan telah dimanfaatkan secara produktif oleh masyarakat. Meskipun demikian, pelaksanaan reforma agraria menghadapi kendala berupa tumpang tindih data aset negara, keterbatasan kewenangan GTRA daerah, serta keterbatasan dukungan sumber daya dan sistem informasi. Secara konseptual, penyelesaian konflik di Nagari Gadut membutuhkan sinergi antara penataan aset dan akses yang melibatkan GTRA pusat, pemerintah daerah, dan masyarakat.